Change in serotonergic modulation contributes to the synaptic imbalance of neuronal circuit at the prefrontal cortex in the 15q11-13 duplication mouse model of autism. (15th March 2020) - Saitow, Fumihito; Takumi, Toru; Suzuki, Hidenori
Abstract: The prefrontal cortex (PFC) has been extensively studied in autism spectrum disorder (ASD) in an attempt to understand the deficits in executive and other higher brain functions related to sociability and emotion. Disruption of the excitatory/inhibitory (E/I) balance of cortical circuits is thought to underlie the pathophysiology of ASD. Recently, we showed that 15q dup mice (a model for ASD with human chromosome 15q11-13 paternal duplication) exhibit disruption of the E/I balance in layer 2/3 pyramidal neurons of the somatosensory cortex due to a decrease in the number of inhibitory synapses. However, whether there is a pathological abnormality in E/I balance in the PFC of 15q dup mice remains unknown. In this study, we found that 15q dup facilitates the activity-induced LTP of glutamate synapses onto layer 5 pyramidal neurons by shifting the E/I balance to an excitatory state, which this was associated with differences in synaptic glutamatergic and GABAergic inputs onto GABAergic fast-spiking interneurons (FSINs). Furthermore, we found that FSIN excitability was well-modulated and regulated by the constitutive activation of 5-HT2 receptors in PFC microcircuits. These results provide new insights into the cellular mechanisms underlying maintenance of optimal E/I balance in the PFC. Highlights: ASD model mice 15q dup exhibit E/I imbalance in L5 PFC pyramidal neurons. Glutamatergic synapses in 15q dup show large synaptic plasticity in the PFC. The E/I imbalance involves synaptic inputs onto FSINs. The E/I balance is also regulated by the activation of 5-HT2A/2C Rs in FSINs.